IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SQ3R TECHNIQUE OF THE FIRST GRADE STUDENTS AT MAN TOLITOLI - Marzuki Marzuki (Jurnal Madako Education, 2017)
The purpose of this study was to find out the empirical evidence concerning whether SQ3R technique was effective or not to teach students reading comprehension. This study was held in March 2015 at MAN Tolitoli. This study used a quantitative method in the design of pre-experimental study.  The sampling technique used in this study was purposive sampling. The researcher took one class as the subject of this study. The sample was X IIS 3. The improvement of students’ score can be seen from the differences between pretest and posttest. The mean score of pretest was 65.88 and it improved to 81.48 in posttest. Moreover, the minimum mastery criterion of English lesson was 76 (seventy-six). Then the data of both test were analyzed by using T-test  and the result showed that the T-test value 8.39 was greater than T-table value 2.064. according to the criteria of the test the result showed that there was a significant improvement between students’ achievement in reading comprehension by using SQ3R technique before and after pretest and posttest were conducted. It meant that SQ3R technique was effective and applicable at the first grade of MAN Tolitoli to teach students’ reading comprehension. Keywords: Improving, Reading, SQ3R technique, Comprehension.